How Did Covid-19 Affect the Structural Relationship between Exchange Rates and Money Supply? Evidence from Malawi - Banda, Fredrick M.; Edriss, Abdi Khalil (International Journal of Economics and Financial Issues, 2023)
For countries that participate in international trade, exchange rate management is crucial as the exchange rate affects the competitiveness of the country in international trade. This affects the country’s balance of payments (BOP) position and economic growth. This paper, therefore, set out to find out how Covid-19 containment measures have affected the Malawi Kwacha-US Dollar exchange rate, as well as money supply. Previous studies have assessed the short-term impacts of Covid-19 on the Malawian economy in general, without considering how they have affected the exchange rate and money supply. This study adds to the literature by analyzing how the Covid-19 containment measures have affected the exchange rate, and consequently, the money supply in Malawi. The study employs the dummy variables approach and the vector error correction (VEC) model to find out if there is a structural change in the exchange rate regression over time and whether that structural change in the exchange rates affects the money supply. Regression results indicate that there is a structural break in the regression over time and that the Malawi Kwacha appreciated following the breakout of the pandemic. Additionally, the results from the Error Correction Model have indicated that the appreciation of the Malawi Kwacha, positively, affected the money supply in Malawi. As a policy implication arising from this study, policymakers are encouraged to take advantage of the prevailing donor goodwill and ensure that the various donations received are put to good use so that the Malawi Kwacha should continue being relatively strong against the United States Dollar. If this is not done, the Malawi Kwacha could, greatly, depreciate, a thing that can make the economy experience inflation thereby making people experience a lot of hardships caused by the Covid-19 pandemic.